Maternal outcome in pregnant women with lupus nephritis. A prospective multicenter study. (November 2016) - Moroni, Gabriella; Doria, Andrea; Giglio, Elisa; Imbasciati, Enrico; Tani, Chiara; Zen, Margherita; Strigini, Francesca; Zaina, Barbara; Tincani, Angela; Gatto, Mariele; de Liso, Federica; Grossi, Claudia; et al.
Abstract: Retrospective studies reported a high incidence of maternal complications in pregnant women with lupus. In this paper we prospectively assessed the rate of risk and the risk factors of maternal outcome in women with stable lupus nephritis who received pre-pregnancy counseling. This prospective multicenter study includes 71 pregnancies in 61 women with lupus nephritis who became pregnant between 2006 and 2013. Complete renal remission was present before pregnancy in 56 cases (78.9%) and mild active nephritis in 15 cases. All women underwent a screening visit before pregnancy and were closely monitored by a multidisciplinary team. Lupus anticoagulant, serum C3 and C4 complement fractions, anti-DNA antibodies, anti-C1q antibodies, anticardiolipin IgG and IgM antibodies, anti-beta2 IgG and IgM antibodies were tested at screening visit, at first, second, third trimester of pregnancy, and one year after delivery. Renal flares of lupus during or after pregnancy, pre-eclampsia, and HELLP syndrome were defined as adverse maternal outcomes. Fourteen flares (19.7%), six cases of pre-eclampsia (8.4%) and two cases of HELLP (2.8%) occurred during the study period. All flares responded to therapy and the manifestations of pre-eclampsia and HELLP were promptly reversible. Low C3, high anti-DNA antibodies and predicted all renal flares. High anti-C1q antibodies and low C4 predicted early flares. The body mass index (BMI) was associated with increased risk of late flares. History of previous renal flares and the presence of clinically active lupus nephritis at conception did not increase the risk of renal flares during pregnancy. History of renal flares before pregnancy, arterial hypertension, and longer disease predicted pre-eclampsia/HELLP. In pregnant women with lupus nephritis adverse maternal outcomes were relatively common but proved to be reversible when promptly diagnosed and treated. Immunological activity, arterial hypertension and BMI may predispose to maternal complications. Highlights: In pregnant women with lupus nephritis adverse maternal outcomes continue to be relatively common. In stable lupus nephritis, pregnancy complications are reversible when promptly diagnosed and treated. Immunological activity, arterial hypertension and BMI predispose to maternal complications. A multidisciplinary monitoring of lupus pregnant women is necessary to minimize maternal complications.